Inovasi dan produktivitas: faktor penentu daya saing umkm di era globalisasi - Daris, Daris (Maliki Interdisciplinary Journal, 2025)
Innovation and productivity are key factors that determine the competitiveness of micro, small, and medium enterprises (msmes) in the era of globalization. Msmes play an important role in the economy with significant contributions to gross domestic product (gdp) and employment. However, global competition and changes in technology and consumer preferences require msmes to continuously innovate and improve productivity. Innovation includes not only new product development but also production processes, marketing, and internal management, which directly affect productivity improvements.Internal factors, such as human resource management, technology, and finance, as well as external factors such as markets, competition, and government policies, also influence the level of innovation and productivity of msmes. With high productivity, msmes can produce quality products at competitive prices, which strengthens their position in the market. The challenges of globalization, such as capital constraints, delays in technology adoption, and market dominance by large firms, need to be addressed with competitiveness-enhancing strategies, including access to capital, strengthening digital infrastructure, and strategic partnerships.